IOT and XBee triggered based adaptive intrusion detection using geophone and quick response by UAV - Samkaria, Rohit; Singh, Rajesh; Gehlot, Anita; Pachauri, Rupendra; Kumar, Amardeep; Singh, Neeraj Kumar; Rawat, Kaushal (International Journal of Engineering and Technology, 2018)
Monitoring of remote areas needs a lot of man power, in this contrast an important additional layer to perimeter protection for home land security application is Seismic footstep detection based systems. This paper mainly concerns with the detection of any human intrusion by the detection of the footsteps from a person from few tens of meters away using an underground seismic sensor, Geophone and placing the intrusion data over the cloud by using IOT. Presence of footstep is indicated by the impulses in the geophone signal. Kurtosis, a statistical measure is used to identify the impulses, can apply for a short duration of time for which a footstep exists. Present method is less complex and computationally efficient, all the input data stored in memory, which are read through microcontroller through ADC and stored in memory is subjected to kurtosis using microcontroller. Many such nodes are connected in a topology to build a Sensor Network. Indication of the intrusion will occur when microcontroller of sensor node calculates higher kurtosis value and will send this value to control room and data is uploaded to cloud at the same time.